Enhancing collaborative interactions between diverse team members - Alkubaisy, Zenah (2019)
Highly pressured working environments can provide a challenging context for collaboration, especially where teams of diverse individuals are formed to tackle short-term projects. Hence, this Ph.D. thesis presents research which explores how to prepare individuals before they meet, so that a group of diverse team members working together for the first time can establish common ground easily and begin to interact collaboratively.